Current Treatments of Binge Eating Disorder - González Calderón, María J.; Ormaechea Alegre, Elena (Pensando Psicología, 2016)
Introduction: Although binge eating disorder (bed) is a major health problem, less than half of sufferers receive treatment.Objective: To review recent literature on interventions carried out in bed cases.Method: In order to conduct this narrative review, the databases PubMed, Medline and Scielo have been consulted. Only articles in indexed journals in the Web of Science were chosen. The literature reviewed corresponds to the most cited articles published in the period between 2010-2015.Results and conclusions: The results show that the most commonly used interventions are those of psychological nature, including cognitive behavioral therapy and interpersonal therapy, the latter recommended in patients with a more severe pathology. The behavioral therapy for weight loss is less effective by not reducing binge eating; therefore, it is not the treatment of choice. Although some antidepressant and antiepileptic drugs have shown some utility in reducing binge eating, weight and comorbidities, there is no evidence that pharmacological intervention alone is more effective than psychological intervention, or that it improves the results of the latter when both are applied together.
Keywords: review; therapy; binge eating disorder; treatment